Schema Theory and Vocabulary Categorization: A Framework for Nursing English - Fitriani; Olivia; Sri Nurlian; Dedi Harfan (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The aim of this study is to investigate how the application of schema-based vocabulary categorization influences nursing students’ comprehension of medical English proficiency. To achieve this objective, a descriptive qualitative method was implemented. The subject in this research was 59 nursing students at STIKES IST Buton. The data were collected through observations, tests, questionnaires, and interviews. The process of data analysis was conducted by categorizing lexical knowledge to enhance contextual analysis. As a result, the point of conclusion is reached. The findings indicate that this method improves students' contextual analysis, resulting in more accurate and professional medical translations. By actively structuring lexical knowledge based on schema theory, this approach offers a practical framework for English for Specific Purposes (ESP) curricula. This study suggests that implementing vocabulary categorization helps nursing students overcome linguistic complexity in a global context, leading to better mastery of medical English.